2021
DOI: 10.1159/000513419
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Inflammation and Calcium Balance of Citrate versus Acetate as Dialysate Buffer in Maintenance Hemodialysis: A Unicentric, Cross-Over, Prospective Study

Abstract: <b><i>Introduction:</i></b> The composition of the dialysate is a crucial feature in the dialysis treatment. Two of its most debated elements are the optimal calcium concentration and the use of acetate as a buffer. Moreover, among the different alternatives to achieve acetate-free dialysis, the use of citrate is postulated as the most suitable option. The objective of this study is to identify the potential beneficial effects of citrate when compared to acetate dialysate (AD) both in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…Metabolomics opens the door to studying human metabolism in response to dialysis-induced changes in intermediary metabolism. This study, performed by a targeted metabolomic approach, found noteworthy differences between dialysates that raise new hypotheses that should be further investigated to explain the deleterious acetate effects on dialysis patients [ 9 , 10 , 11 , 12 , 13 ]. Acetyl-CoA levels exceeded by 20–70 times the physiological level despite the apparently small concentrations of acetate in the AD [ 8 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolomics opens the door to studying human metabolism in response to dialysis-induced changes in intermediary metabolism. This study, performed by a targeted metabolomic approach, found noteworthy differences between dialysates that raise new hypotheses that should be further investigated to explain the deleterious acetate effects on dialysis patients [ 9 , 10 , 11 , 12 , 13 ]. Acetyl-CoA levels exceeded by 20–70 times the physiological level despite the apparently small concentrations of acetate in the AD [ 8 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, and to make the treatment parameters as similar as possible, bicarbonate and sodium concentration in both dialysates were adjusted in the monitor to 32 and 138 mmol/L, respectively. More details on the parameters of the dialysis treatments have been published previously [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a crossover, prospective study of 21 hemodialysis patients found that dialysis with citrate dialysate (containing 3.0 mEq/L of calcium) resulted in stable ionized calcium levels, a neutral-to-negative effect on calcium balance, and reductions in inflammatory biomarkers relative to those effects observed with acetate dialysate (containing 3.0 mEq/L of calcium). 28 …”
Section: Discussionmentioning
confidence: 99%
“…Data processing was done using an in-house R (v.3.6.1) processing script with XCMS and CAMERA packages for peak detection, noise filtering, alignment and normalization. Parameters selected were: CentWave method (noise = 1,000; Adapted from (Broseta et al, 2021) Frontiers in Physiology frontiersin.org ppm = 50; k = 5; I = 300; snthresh = 10; min = 6; max = 25; integrate = 2; nS = 4); matching peaks across samples (grouping): Density method (mzwid = 0.05; bw = 1; mF = 0.5; mS = 1); retention time correction (m = 0; e = 0); integration of samples: FillPeaks method; median fold change normalisation: medFC technique; and CAMERA isotopes: FindIsotopes. The data matrix finally obtained was composed of molecular features consisting of two values: accurate mass (m/z) and retention time (min).…”
Section: Data Pre-processingmentioning
confidence: 99%